Relationships Between Trust, Organizational Justice and Performance Appraisal Satisfaction: Evidence from Public Higher Educational Institution in Malaysia - ., Saraih; N, U; Karim, Mohd; ., K; Hanie Abu Samah, Irza; ., Amlus; H, M; Nazima Abashah, Aida (International Journal of Engineering and Technology, 2018)
The main objective of this present study is to reveal the role of trust as a mediator in the relationship between organizational justice and performance appraisal satisfaction. This study is carried out by distributing questionnaire among 340 staffs. In this research, the questionnaire is administered to staffs from various schools in one of the Malaysian Public Higher Educational Institution (PHEI). Data are analysed by using the PROCESS (Hayes, 2013). As a result, a significant effect of organizational justice on performance appraisal satisfaction with trust as the mediator F(2, 337)=.396, p<.01, R2=.7016, Î²=.7813, t(337)=21.29, p<.01 is found in this study. A Sobel test is conducted and found a mediation on the model (z=3.2447, p=.00, K2=.0213). Therefore, it is found that trust mediated the relationship between organizational justice and performance appraisal satisfaction. Cultivating the degree of trust among staffs towards the performance appraisal satisfaction; and creating a conductive environment for staffs to improve their perceived organizational justice are the best strategies to achieve the goal for performance appraisal satisfaction in this institution. Theoretical and practical implications based on the results of this study are highlighted. In this line, few suggestions for the institution management are provided.Â